A hospital's collaborative arts in health approach to COVID-19. (1st December 2021) - Kulha, Shay Thornton; Frazier, J. Todd; Townsend, Jennifer; Laguaite, Elizabeth; Gray, Virginia
This note from the field outlines how an integrated arts in health department within a hospital created clinical and non-clinical art experiences for patients and providers during COVID-19. Working with a multi-disciplinary team, the Center for Performing Arts Medicine at Houston Methodist established creative arts therapy and arts integration programmes targeting patient and provider experiences during COVID-19. Emphasis is placed on how programmes respond to both physical health and emotional well-being through accessible, appropriate art experiences. This article outlines those strategies and highlights various entry points for arts experiences in a hospital experience during a pandemic.